Autism, theory of mind, and the reactive attitudes. (15th September 2017) - Richman, Kenneth A.; Bidshahri, Raya
Abstract: Whether to treat autism as exculpatory in any given circumstance appears to be influenced both by models of autism and by theories of moral responsibility. This article looks at one particular combination of theories: autism as theory of mind challenges and moral responsibility as requiring appropriate experience of the reactive attitudes. In pursuing this particular combination of ideas, we do not intend to endorse them. Our goal is, instead, to explore the implications of this combination of especially prominent ideas about autism and about moral responsibility. These implications can be quite serious and practical for autists and those who interact directly with autists, as well as for broader communities as they attend to the fair, compassionate, and respectful treatment of increasing numbers of autistic adults. We find that these theories point to a limited range of situations in which autists should not be blamed for transgressive actions for which neurotypical individuals should be blamed. We build on what others have written on these issues by bringing in a recent cognitive model of the role theory of mind plays in empathy, by discussing the social implications of the theoretical findings, and by raising questions about the compatibility of reactive attitude theories of moral responsibility with the neurodiversity approach to autism.